Enhancing Awareness of Fish-Based Nutrition: Processed Fish Products Education at Aisyiyah Orphanage, Malang - Abdul Aziz Jaziri; Rahmi Nurdiani; Hefti Salis Yufidasari; Retno Tri Astuti; Eko Waluyo; Tian Nur Ma'rifat; Ahmad Syihab Fahmi; Angga Wira Perdana; Bayu Kusuma; Sukoso Sukoso; Happy Nursyam; Asep Awaludin Prihanto; Dwi Setijawati; Muhamad Firdaus (Indonesian Journal of Community Services, 2026)
This community service program was conducted at Aisyiyah Orphanage in Malang to improve nutritional knowledge, practical skills in fish processing, and healthy eating habits among students. A total of 31 students, orphanage caregivers, and faculty members from the Program of Fishery Product Technology, Universitas Brawijaya participated, reflecting a collaborative model of knowledge transfer and community engagement. Activities were structured into socialization, educational presentations, interactive discussions, hands-on demonstrations, evaluation, and follow-up planning. A pre-test assessed baseline knowledge of fish species, handling, nutrition, and processed products. Results showed that while students were generally aware of nutrition, they lacked technical understanding of processing methods and functional ingredients. Educational sessions and peer-led demonstrations addressed these gaps through the preparation of fish balls, nuggets, and gohyong, supported by recipe modules to encourage independent practice. Post-test scores demonstrated significant improvements, particularly in areas previously identified as weak, confirming the effectiveness of combining theory with practice. The follow-up phase emphasized sustainability by embedding food preparation into daily routines and encouraging entrepreneurial opportunities in fish product marketing. Overall, the program demonstrated that multi-component, participatory interventions can enhance knowledge, skills, and confidence, while promoting healthier eating behaviors and community empowerment among vulnerable youth.